Analysis of Deixis in The Short Story “The Garden of Paradise”: Pragmatics Study - Puspaningrum, Aprilia; Simatupang, Ervina (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
The study aims to investigate the various forms of deixis and their roles within the short story "The Garden of Paradise." Using a qualitative descriptive approach, the author employs Cresswell's (2013) theoretical framework. The data analysis is based on pragmatic theories by Griffiths (2006) and deixis theories by Yule (1996), Cruse (2000), Bouk (2016), and Levinson (1983). The findings reveal: (1) A total of 202 instances of deixis in the short story, categorized into five types, including 89 (44%) instances of person deixis, 31 (15,34%) of spatial deixis, 37 (18,31%) of time deixis, 35 (17,32%) of discourse deixis, and 10 (5,03%) of social deixis. (2) Each type of deixis has distinct functions: person deixis clarifies the roles of participants in speech acts, spatial deixis indicates the relative locations of speakers and listeners, time deixis specifies when the speech occurs, discourse deixis relates to elements within the speech act discourse, and social deixis highlights aspects of the social relationship between speakers and listeners.